Computer Graphics : Principles and practice - Hughes, John F.; Dam, Andries Van (New Jersey Pearson Education, 2014)
The authors explain the principles, as well as the mathematics, underlying computer graphics-knowledge that is essential for successful work both now and in the future. Early chapters show how to create 2D and 3D pictures right away, supporting experimentation. Later chapters, covering a broad range of topics, demonstrate more sophisticated approaches. Sections on current computer graphics practice show how to apply given principles in common situations, such as how to approximate an ideal solution on available hardware, or how to represent a data structure more efficiently.
Includes bibliographical references and index
Keywords: Công nghệ thông tin